Character Education in Islam - Khairani Al Fatha; M. Billy Kurniawan; Mutiya; Muhammad Shaleh Assingkily (Yayasan Zia Salsabila, 2023)
Character education and moral crises are familiar to educators. Likewise society in general, especially in this increasingly global era. Therefore, character education is very much needed to restore the character of society in general and Muslims in particular through character education for the better character of Muslim generations in the future. This paper aims to analyze character education in Islam. This study uses a qualitative descriptive approach, and the type of research used is library research, which collects data or scientific papers related to the research object or library data collection. Based on this research, it was found that (1) character education has an important role in improving and shaping the personality of students who are imbued with faith and piety to God Almighty; and (2) supporting components in character education are parental assistance and support, community participation, and policies in the world of education. In the application and development of character education can be explored from religion and developed through the stages of knowledge, implementation, and habits.